A Go-type opsin mediates the shadow reflex in the annelid Platynereis dumerilii - Thomas Ayers; Hisao Tsukamoto; Martin Gühmann; Vinoth Babu Veedin Rajan; Kristin Tessmar-Raible (BMC Biology, 2018)
Abstract Background The presence of photoreceptive molecules outside the eye is widespread among animals, yet their functions in the periphery are less well understood. Marine organisms, such as annelid worms, exhibit a ‘shadow reflex’, a defensive withdrawal behaviour triggered by a decrease in illumination. Herein, we examine the cellular and molecular underpinnings of this response, identifying a role for a photoreceptor molecule of the Go-opsin class in the shadow response of the marine bristle worm Platynereis dumerilii. Results We found Pdu-Go-opsin1 expression in single specialised cells located in adult Platynereis head and trunk appendages, known as cirri. Using gene knock-out technology and ablation approaches, we show that the presence of Go-opsin1 and the cirri is necessary for the shadow reflex. Consistently, quantification of the shadow reflex reveals a chromatic dependence upon light of approximately 500 nm in wavelength, matching the photoexcitation characteristics of the Platynereis Go-opsin1. However, the loss of Go-opsin1 does not abolish the shadow reflex completely, suggesting the existence of a compensatory mechanism, possibly acting through a ciliary-type opsin, Pdu-c-opsin2, with a Lambdamax of approximately 490 nm. Conclusions We show that a Go-opsin is necessary for the shadow reflex in a marine annelid, describing a functional example for a peripherally expressed photoreceptor, and suggesting that, in different species, distinct opsins contribute to varying degrees to the shadow reflex.